Biological Properties of Streptococcus pluranimalium as the New Human Pathogen - Ananieva, Maiia; Faustova, Mariia; Loban, Galina; Avetikov, Davyd; Tkachenko, Pavlo; Bobyr, Vitalii; Dobrovolska, Oksana (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: The limited amount of information available today does not fully reflect the biological properties of Streptococcus pluranimalium as a pathogen new to humans, its pathogenicity factors, and, as a consequence, the pathogenesis of diseases, which is causes AIM: The aim of this research was to study the biological properties of S. pluranimalium, its sensitivity to antibiotics and antiseptics, as well as its adhesive properties. METHODS: Two hundred samples were collected from the coronal pockets in patients with acute purulent pericoronitis during 2019–2021 years. Among them, five clinical strains of S. pluranimalium were isolated. Final identification was carried out using a Vitec-2compact bioMérieux automatic bacteriological analyzer. The sensitivity of the studied microbial strains to antibiotics of various groups was determined by the disk diffusion method. The adhesive properties of S. pluranimalium were determined according to the standard Brilis method. RESULTS: It possesses typical morphological and cultural properties characteristics of the genus Streptococcus representatives. This microorganism virtually does not break down carbohydrates, but it produces arylamidases that enables it to be differentiated from other streptococci. S. pluranimalium demonstrates variable sensitivity to antibiotics; the lowest sensitivity has been found out to the second-generation fluoroquinolones. In addition, the clinical isolates studied show high adhesive properties to human red blood cells. CONCLUSIONS: S. pluranimalium is increasingly acting as the causative agent of human infectious diseases. The information available today fully reflects the biological properties of a pathogen new to humans, its pathogenicity factors.